FINANCIAL STATEMENT ANALYSIS USING THE TREND ANALYSIS METHOD TO EVALUATE THE FINANCIAL PERFORMANCE OF PT PGN (PERSERO) TBK FOR THE PERIOD 2018–2022 - Jalil, Muhammad; Sandra; Taufik kurahman; winda suriyati; Yuli Wardani Putri (Indragiri Research Center (ingreat), 2025)
This research is motivated by the fluctuating financial performance of PT PGN (Persero) Tbk as reflected in its income statements during the 2018–2022 period. As a company operating in the energy sector, PT PGN faces challenges related to operational costs and government-regulated industrial gas pricing. The purpose of this study is to evaluate the company’s financial trends by analyzing key components of its income statement, including net revenue, gross profit, and operating income. The study employs a descriptive quantitative method with trend analysis applied to secondary data obtained from annual financial statements. The goal is to observe the financial movement patterns across the five-year period. The results indicate that the company’s revenue and profit figures have fluctuated significantly. Declines in certain years were due to high gas procurement costs and reduced consumption from industrial clients, while improvements in other years suggest successful cost management. Despite these fluctuations, the company maintained its operational viability. It is concluded that trend analysis is a valuable tool in assessing a company’s financial health and can inform strategic decision-making by management.